Semiotic Analysis of Moral Messages in Animated Film Raya and The Last Dragon - Afifah Ibna Fatina Tawakkal; Agnes Tasya Monix; Emirson Watani (NOTION: Journal of Linguistics, Literature, and Culture, 2021)
Raya and The Last Dragon is the latest computer-animated film from Walt Disney Pictures and Walt Disney Animation Studio. This animated film, directed by Don Hall and Carlos Lopez, tells the story of the adventures of a woman named Raya in saving the world. This journal article aims to analyze and describe the moral messages contained in the film Raya and The Last Dragon. This research uses qualitative methods, with Roland Barthes semiotics analysis approach, so that ultimately obtained the results of research on what moral messages contained in every dialogue spoken by each character such as moral messages about friendship, cooperation, responsibility, leadership, courage, unity, and most often appears in this film is the power of trust in each other to create unity without division.